Philosophy - Stangroom, Jeremy (London : A&C Black, 2008)
Offers a collection of short entries that provides brief profiles of fifty prominent figures and explanations of ten key concepts in the field of philosophy.
Includes index.
Adult
Keywords: Philosophy -- Introductions; Philosophy